(untitled) (Bioscience Journal, 2018)
Micronutrients play a vital role in the growth and productivity of cotton crop. A study was carried out to access the exogenous application of micronutrients on growth and yield of cotton crop. The experiment was comprised of nine treatments as T0 (control), T1 (Fe chelated), T2 (B), T3 (Mo), T4 (CuSo4 + ZnSo4 + MnSo4), T5 (CuSo4 + ZnSo4 + MnSo4 + Fe chelated), T6 (CuSo4 + ZnSo4 + MnSo4 + B), T7 (CuSo4 + ZnSo4 + MnSo4 + Mo) and T8 (CuSo4 + ZnSo4 + MnSo4 + Fe chelated + B). Data on different growth attributes showed that there was significant positive increase with the application of micronutrients. Leaf area was increased after applying micronutrients at 99 days after sowing (DAS) and then a decreasing trend was observed. Chlorophyll contents were increased at 81 DAS and then decreased towards the final harvest. Similarly, different yield components showed that seed cotton yield were significantly increased with the application of Fe, B, Mo, Zn, Cu and Mn compared to control treatment. Earliness index, mean maturity date and production rate index were increased significantly after combined use of foliar spray of Zn, Cu, Mn and Mo.